Impact of catalyst loading, ionomer content, and carbon support on the performance of direct isopropanol fuel cells - Hauenstein, Pascal; Mangoufis Giasin, Iosif; Seeberger, Dominik; Wasserscheid, Peter; Mayrhofer, Karl; Katsounaros, Ioannis; Thiele, Simon (Journal of Power Sources Advances, 2021)
Liquid Organic Hydrogen Carriers (LOHC) offer a promising solution for hydrogen storage in the existing infrastructure for conventional fuels. Within this framework, the isopropanol/acetone couple as a light-LOHC system is used to generate electricity in a direct isopropanol fuel cell (DIFC). This work focuses on the impact of catalyst loading, ionomer content and catalyst support on the performance of DIFCs. We achieve a performance rise from 95 mW cm-2 to 219 mW cm-2 under air operation by increasing the anode catalyst loading from 0.5 mg cm-2 to 4 mg cm-2, which can be attributed to the increased abundance of active catalyst sites with higher loadings. In contrast, we find that the cathode loading for the oxygen reduction reaction (ORR) plays a minor role in the performance of DIFCs. Therefore, the cathode loading can be minimized to decrease the total amount of platinum-group metals and, consequently, to save cost. It was also found that an ionomer content of 30% on the anode side is optimal. Additionally, different carbon supports were investigated, where advanced high surface area carbon support showed superior performance to Vulcan with an increase of 20% in power density, motivating the development of new carbon supports for DIFCs.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 2-propanol fuel cell; Carbon support; Catalyst loading; Direct isopropanol fuel cells; Ionomer content; LOHC; Organic fuel cells